Physiological and Pathological Aging Affects Chromatin Dynamics, Structure and Function at the Nuclear Edge - Robin, Jérôme D.; Magdinier, Frédérique (Frontiers in Genetics, 2016)
Lamins are intermediate filaments that form a complex meshwork at the inner nuclear membrane. Mammalian cells express two types of Lamins, Lamins A/C and Lamins B, encoded by three different genes, LMNA, LMNB1 and LMNB2. Mutations in the LMNA gene are associated with a group of phenotypically diverse diseases referred to as laminopathies. Lamins interact with a large number of binding partners including proteins of the nuclear envelope but also chromatin-associated factors. Lamins not only constitute a scaffold for nuclear shape, rigidity and resistance to stress but also contribute to the organization of chromatin and chromosomal domains. We will discuss here the impact of A-type Lamins loss on alterations of chromatin organization and formation of chromatin domains and how disorganization of the lamina contributes to the patho-physiology of premature ageing syndromes.